The feed analysis laboratory : establishment and quality control : setting up a feed analysis laboratory, and implementing a quality assurance system compliant with ISO/IEC 17025:2005 - Jonge, L. H. de.; Jackson, F. S.; Makkar, Harinder P. S. (Rome : Food and Agriculture Organization of the United Nations, 2013)
"The aim of this present document is to present guidelines for starting and running an animal feed analysis laboratory, including the implementation of quality assurance (QA) systems compliant with an international standard. To achieve this goal, the relevant information will be described and illustrated by giving examples wherever appropriate, which should lead to a better understanding by semi-technical persons and decision-makers."--P. 1.
Keywords: Feeds -- Analysis; Feeds -- Composition; Animal nutrition; Animal feeding